Designing Self-Management Features for Digital Islamic Spiritual Health Interventions for Adolescents with Sexual Behavior Problems - Mohd Noh, Mohd Amin; Mat Noor, Siti Fadzilah; Judi, Hairulliza Mohamad; Mat Zin, Nor Azan; @Ashaari, Noraidah Sahari (Jurnal Ilmiah Peuradeun, 2025)
Digital health interventions (DHIs) have the potential to provide culturally relevant, private support for adolescent sexual behavior problems (SBPs), yet few are designed for Muslim-majority contexts. In Malaysia, the absence of an Islamic-values-based self-management intervention (SmI) model limits the integration of faith-based principles in adolescent health interventions. This study applies the TUDER framework (Targeting and Understanding) to map existing DHIs and identify key features for an Islamic-values-based SmI design. A web search conducted from January to April 2024 identified 53 platforms across Malaysia and neighboring countries, categorized by service type and features. Semi-structured interviews with nine experts in adolescent health and Islamic spiritual interventions were analyzed thematically using Braun and Clarke’s six-step process. Seven key design features—privacy, relaxation, lighthearted tone, catchiness, humor, confidence-boosting, and infographics—emerged as critical for engaging adolescents in conservative contexts. These features align with Islamic psychospiritual principles like tazkiyah al-nafs (spiritual purification). This study proposes a conceptual SmI framework that integrates these features with persuasive system design, offering a novel approach for developing culturally grounded DHIs. The framework strengthens the theoretical foundation for Islamic-values-based interventions and can be adapted to similar settings in Muslim-majority countries.